Development and optimization of enzalutamide nanosuspension by design of experiments for dissolution enhancement (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Enzalutamide is an anticancer molecule used for prostate cancer. The goal of the study was to develop a nanosuspension of enzalutamide in order to improve its solubility and dissolution properties. High speed homogenization method was employed to formulate the nanosuspension. Preliminary studies suggested amount of stabilizer, homogenization time and homogenization speed as critical variables to be taken for the optimization process. Box-Behnken design was employed for the optimization of process and formulation variables. Nanosuspension was evaluated for particle size, PDI, zeta potential, and in vitro drug release at 10 min (D10) studies. Regression analysis suggested the influence of independent variables on the responses. The optimized batch obtained from overlay plot exhibited 198.36 nm of particle size, (-33.27 mV of zeta potential and 80.47 % of D10 values. The characterization studies i.e. DSC, and XRD illustrated retention in crystallinity of drug. The drug and formulation were found to be stable over a 6-month period in accelerated stability testing. Using high speed homogenization method, particle size of the formulation was reduced to nano-size which was further responsible for the improvement in dissolution and bioavailability of drug.